2016
DOI: 10.18533/jefs.v4i3.236
|View full text |Cite
|
Sign up to set email alerts
|

Banking Access for the Poor: Adoption and Strategies in Rural Areas of Bangladesh

Abstract: The progress of Mobile Banking (M-banking) is unsatisfactory in terms of achieving a key objective, i.e. to reach the inaccessible unbanked customers at an affordable cost for financial inclusion. We identify the causes to this problem through the investigating the factors affecting the adoption of m-banking in remote areas of Bangladesh using a 236 primary sample of m-bank customers from seven geographical locations and across professions. We document a positive effect of perceived ease of use, trusts, and pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
2
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 34 publications
1
2
0
2
Order By: Relevance
“…A previous study showed that perceived usefulness has a positive influence on actual usage within the context of intranet technology (Lee & Kim, 2009). This finding is similar to results in various other studies (Kim et al, 2007;Rahman et al, 2016;Kripanont, 2007;Norzaidi et al, 2007).…”
Section: Literature Review Perceived Usefulnesssupporting
confidence: 85%
“…A previous study showed that perceived usefulness has a positive influence on actual usage within the context of intranet technology (Lee & Kim, 2009). This finding is similar to results in various other studies (Kim et al, 2007;Rahman et al, 2016;Kripanont, 2007;Norzaidi et al, 2007).…”
Section: Literature Review Perceived Usefulnesssupporting
confidence: 85%
“…(2014) stated that there are few positive perceptions on the ease of use in which they noted that most of the academic staff has experience in using computer for more than 10 years and adopting blended learning among them is not a problem. Anisur et al (2016) in their study found that there is a positive correlation between perceived ease of use and system usage. In addition, Osama et al (2016), noted that perceived ease of use has the highest score of mean indicated that respondents considered that blended learning is easy to use, understandable and flexible.…”
Section: Perceived Ease Of Usementioning
confidence: 90%
“…TAM, which was introduced by Fred D. Davis in 1986, is considered to be the greatest influential theory describing the acceptance of information systems (Lee et al, 2003). A well-known theory on the use and prediction of information technology acceptance, its capability has been validated by several studies in the domain of e-learning (Lee et al, 2011;Padilla-Meléndez et al, 2013;Lee et al, 2014;Tarhini et al, 2014;Wu and Zhang, 2014;Al-Gahtani, 2016;Rahman et al, 2016). The model is rooted in the Theory of Reasoned Action and Theory of Planned Behavior which were proposed by Ajzen and Fishbein (1980), Sarcheshmeh et al (2018), andAjzen (1985), respectively, under the theories of Social Psychology (Al-Fraihat et al, 2020).…”
Section: Literature Review 21 Technology Acceptance Model (Tam)mentioning
confidence: 99%